EUV-permeable film

By using metal beryllium as the main layer and forming a fluoride surface layer on its surface, the durability problem of the EUV transmissive membrane in a low-pressure hydrogen atmosphere environment and the problem of particles generated during damage are solved, and high EUV transmittance and accurate pattern transfer are achieved.

CN119790350APending Publication Date: 2025-04-08NGK INSULATORS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280005706.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing EUV permeable membrane lacks durability in a low-pressure hydrogen atmosphere environment, and particles are easily generated when the membrane is damaged, affecting the accuracy of pattern transfer.

Method used

The main layer composed of metal beryllium and a surface layer containing fluoride are combined to form a fluoride surface layer by fluorination treatment, and the difference in the thickness and fluorine atom concentration of the surface layer are controlled to achieve high EUV transmittance and durability of the film.

Benefits of technology

It realizes the EUV-permeable membrane with high durability in a low-pressure hydrogen atmosphere environment, and avoids the generation of particles when the membrane is damaged, ensuring the accuracy and production efficiency of pattern transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790350A_ABST
    Figure CN119790350A_ABST
Patent Text Reader

Abstract

Provided is an EUV-permeable film which is not susceptible to the generation of particles even if the film is damaged. This EUV-permeable film is provided with: a main layer comprising beryllium metal and having a first surface and a second surface; and a pair of surface layers that are provided on the first surface and the second surface of the main layer, and that contain at least one fluoride selected from the group consisting of beryllium fluoride, beryllium nitride, beryllium fluoride oxide, and beryllium nitride fluoride oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an EUV transparent film. Background Art

[0002] The miniaturization of semiconductor manufacturing technology is advancing year by year. In order to develop the technology of miniaturization, many processes in semiconductor manufacturing are being improved. Among them, in the exposure process, EUV (extreme ultraviolet) light with a wavelength of 13.5nm is used to replace the wavelength of 193nm of the previous ArF exposure. By changing from ArF light to EUV light, the wavelength is reduced to less than 1 / 10, and the optical properties of EUV light are completely different from those of ArF light. Therefore, a lot of technical development is required. In particular, with respect to the protective member (pellicle) as the particle adhesion prevention film of the photomask (reticle), it is expected to develop a protective member with high EUV transmittance. At present, there is no protective member with high transmittance for EUV light. When using the existing protective member, there are the following problems, that is, when EUV light passes through the protective member, the EUV light intensity is greatly reduced, the exposure time becomes longer, resulting in reduced throughput, or the protective member absorbs EUV light and reaches a high temperature, and deteriorates in a short time.

[0003] Therefore, the development of protective films is carried out. For example, Patent Document 1 (Japanese Patent Gazette No. 6858817) discloses a protective film, which comprises: a core layer, which contains a material such as (Poly)Si that is substantially transparent to EUV radiation; and an overlying layer, which contains a material that absorbs IR radiation. However, when the Poly-Si-based protective film is set to a thickness for maintaining film strength, the EUV transmittance cannot reach the target, i.e., 90%, and has not been practical so far. In addition, a carbon nanotube (CNT)-based protective film has also been developed (Patent Document 2 (Japanese Patent Gazette No. 2018-194840)), and higher EUV transmittance is expected.

[0004] However, the protective film may be damaged during use, and countermeasures are required to ensure that the pattern transfer will not be affected even in this case. For example, Patent Document 3 (Japanese Patent Publication No. 2018-537720) discloses a protective film having a damaged area that is preferentially damaged during normal use in a lithography device. Accordingly, the position where the damage first occurs is set in advance on the protective film. In addition, the document also discloses a method for monitoring the damage of the protective film, a method for preventing the damage from developing when damage is detected, and a method for rolling up the film by utilizing the tension difference in the thickness direction of the protective film when the protective film is damaged.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6858817

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-194840

[0009] Patent Document 3: Japanese Patent Application No. 2018-537720 Summary of the invention

[0010] However, the actual situation of CNT-based protective films, for example, is that they lack durability in the environment in which the protective parts are used (low-pressure hydrogen atmosphere). When the protective film is covered with metal to make it durable, the EUV transmittance decreases and the transmittance at a practical level cannot be achieved. Therefore, device manufacturers have no choice but to use EUV exposure for production without using a protective film. In particular, Patent Document 3 does not disclose the specific material, film thickness, stress, etc. of the protective film. At this time, the state of the protective film when it is damaged varies depending on the properties of the protective film used. Therefore, it is expected to properly control the properties of the protective film used so that even when the protective film is damaged, it will not affect the pattern transfer. As such, the performance required of the protective film includes various properties such as high EUV transmittance and in-plane uniformity of EUV transmittance, durability in a low-pressure hydrogen atmosphere environment, and in particular, it is particularly expected that particles will not be generated even if the protective film is damaged. If the protective film is damaged and particles are generated, the particles will adhere to the optical network, reflector, etc. and cause pattern transfer errors. In addition, if particles adhere to the optical reticle, the photomask needs to be cleaned; if particles adhere to the exposure device, the exposure device needs to be cleaned. When the exposure device is cleaned, the device stops for a long time, and the device manufacturer loses more money, etc. Therefore, it is desired to have an EUV transmission film as a protective film that is not easy to generate particles even if it is damaged.

[0011] The inventors of the present invention have recently found that a combination of a main layer composed of metal beryllium and a pair of surface layers containing fluoride can provide an EUV transparent film that is less likely to generate particles even if the film is damaged.

[0012] Therefore, an object of the present invention is to provide an EUV transmitting film in which particles are unlikely to be generated even if the film is damaged.

[0013] According to the present invention, the following solutions are provided.

[0014] [Solution 1]

[0015] An EUV transparent film, comprising:

[0016] a main layer, the main layer being composed of metal beryllium and having a first surface and a second surface; and

[0017] A pair of surface layers, the pair of surface layers are provided on the first surface and the second surface of the main layer, and contain at least one fluoride selected from the group consisting of beryllium fluoride, beryllium fluoronitride, beryllium oxyfluoride, and beryllium oxynitride fluoride.

[0018] [Solution 2]

[0019] The EUV transparent film according to claim 1, wherein

[0020] The surface layer includes beryllium fluoride.

[0021] [Solution 3]

[0022] The EUV transparent film according to claim 1 or 2, wherein

[0023] The surface layer includes beryllium fluoronitride.

[0024] [Solution 4]

[0025] The EUV transparent film according to any one of items 1 to 3, wherein

[0026] The surface layer includes beryllium oxyfluoride.

[0027] [Solution 5]

[0028] The EUV transparent film according to any one of items 1 to 4, wherein

[0029] The surface layer includes beryllium oxyfluoride and nitride.

[0030] [Solution 6]

[0031] The EUV transparent film according to any one of items 1 to 5, wherein

[0032] The surface layer further includes at least one selected from the group consisting of beryllium nitride, beryllium oxynitride, and beryllium oxide.

[0033] [Solution 7]

[0034] The EUV transparent film according to claim 6, wherein

[0035] The surface layer includes beryllium fluoride and beryllium nitride.

[0036] [Scheme 8]

[0037] The EUV transparent film according to claim 6 or 7, wherein

[0038] The surface layer includes beryllium fluoride and beryllium oxynitride.

[0039] [Solution 9]

[0040] The EUV transparent film according to any one of items 6 to 8, wherein

[0041] The surface layer includes beryllium fluoride and beryllium oxide.

[0042] [Scheme 10]

[0043] The EUV transparent film according to any one of items 6 to 9, wherein

[0044] The surface layer includes beryllium fluoride, beryllium oxide and beryllium nitride.

[0045] [Scheme 11]

[0046] The EUV transparent film according to any one of items 1 to 10, wherein

[0047] The thickness of the surface layer at the first surface is 1.1 times or more the thickness of the surface layer at the second surface.

[0048] [Scheme 12]

[0049] The EUV transparent film according to any one of items 1 to 11, wherein

[0050] The fluorine atom concentration at the outermost surface of the surface layer on the first surface side is 1.5 times or more the fluorine atom concentration at the outermost surface of the surface layer on the second surface side.

[0051] [Scheme 13]

[0052] The EUV transparent film according to any one of items 1 to 12, wherein

[0053] The thickness of the surface layer at the first surface is greater than the thickness of the surface layer at the second surface, and the fluorine atom concentration at the outermost surface of the surface layer on the first surface side is higher than the fluorine atom concentration at the outermost surface of the surface layer on the second surface side,

[0054] When the ratio of the thickness of the surface layer at the first surface to the thickness of the surface layer at the second surface is set to A, and the ratio of the fluorine atom concentration at the outermost surface of the surface layer on the first surface side to the fluorine atom concentration at the outermost surface of the surface layer on the second surface side is set to B, A×B≥2.0 is satisfied. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a schematic cross-sectional view showing one form of the EUV transmitting film of the present invention.

[0056] Figure 2A It is a schematic cross-sectional view showing a state before the EUV transparent film is damaged.

[0057] Figure 2BThis is a schematic cross-sectional view showing a state where a conventional EUV transmitting film is damaged.

[0058] Figure 2C It is a schematic cross-sectional view showing a state where the EUV transmitting film of the present invention is damaged.

[0059] Figure 3A This is a process flow chart showing the first half of the manufacturing steps of the EUV transparent film in Example 2.

[0060] Figure 3B This is a process flow chart showing the second half of the manufacturing steps of the EUV transparent film in Example 2. DETAILED DESCRIPTION

[0061] EUV transparent film

[0062] Figure 1 , a simplified cross-sectional view of an EUV transparent film 10 according to one embodiment of the present invention is shown. The EUV transparent film 10 comprises: a main layer 12, and a pair of surface layers 14 arranged on both sides thereof. That is, the main layer 12 has a first surface 12a and a second surface 12b, and the surface layer 14 is respectively arranged on the first surface 12a and the second surface 12b. The main layer 12 is composed of metal beryllium, and the surface layer 14 contains at least one fluoride selected from beryllium fluoride, beryllium fluoride nitride, beryllium fluoride oxide and beryllium fluoride nitride oxide. It is particularly preferred that a large amount of fluoride is included on the outermost surface of the surface layer 14. By combining the main layer 12 composed of metal beryllium and a pair of surface layers 14 containing fluoride in this way, it is possible to provide an EUV transparent film 10 that is not prone to generate particles even if the film is damaged.

[0063] That is, as described above, the performance required of the pellicle includes various performances such as high EUV transmittance and durability in a low-pressure hydrogen atmosphere. In particular, it is particularly desired that particles are not generated even when the pellicle is damaged. If the pellicle is damaged and particles are generated, the particles will adhere to the optical grid, reflective mirrors, etc., causing pattern transfer errors. In addition, if the particles adhere to the optical grid, the photomask needs to be cleaned; if the particles adhere to the exposure device, the exposure device needs to be cleaned. When the exposure device is cleaned, the device stops for a long time, and the device manufacturer loses a lot of money. According to the EUV transparent film 10 of the present invention, the above problems are successfully solved. The mechanism of particle generation when the pellicle is damaged is described in detail below. First, the size of the EUV transparent film is typically about 110×140 mm. However, at this time, the gap between the optical grid and the EUV transparent film is only 2 to 3 mm. Therefore, depending on the state of the EUV transparent film after damage, the EUV transparent film contacts the optical grid, thereby generating particles from the damaged part of the EUV transparent film, and the particles may adhere to the optical grid. For example, a self-supporting film as the EUV transparent film 10 of the present invention (or the conventional EUV transparent film 110) can be typically produced as follows, that is, after forming a laminated film to be made into the EUV transparent film 10 on a substrate (e.g., a Si substrate) used in film formation, the unnecessary portion of the Si substrate is removed by etching with XeF2 to achieve a self-supporting film. Figure 2A As shown, the substrate used in film formation remains in the form of a border 16 at the outer edge of the EUV transparent film 10 or 110, and an optical mesh 18 is arranged at the border 16 on the opposite side of the EUV transparent film 10 or 110. Figure 2B As shown in FIG. 1 , when the conventional EUV transmitting film 110 is damaged, the damaged portion of the EUV transmitting film 110 is in a floating state, and contacts the optical reticle 18 , thereby generating particles P.

[0064] In contrast, the EUV transparent film 10 according to the present invention is Figure 2CAs shown, the EUV transparent film 10 is rolled up toward the first surface side (the side opposite to the optical grid side) so that it does not contact the optical grid 18. The reasons why the EUV transparent film 10 of the present invention performs the above-mentioned behavior are explained below. First, as the material of the EUV transparent film 10, metal beryllium with high EUV transmittance is used for the main layer. However, since the reactivity between metal beryllium and the XeF2 gas used for etching is high, an overcoat layer is formed on both sides (the first side 12a and the second side 12b) of the main layer 12 in order to suppress the reaction. During etching, the XeF2 gas reacts with the overcoat layer, and at least a portion of the overcoat layer is fluorinated to form a fluoride, thereby forming the above-mentioned pair of surface layers 14 on both sides of the main layer 12. By including fluoride in the surface layer 14 in this way, the stress of the pair of surface layers 14 can be controlled, so that there is a difference in stress at the two sides of the EUV transparent film 10, and thus, when the EUV transparent film is damaged, the EUV transparent film is rolled up by utilizing the stress difference. According to this, it is possible to provide the EUV transparent film 10 which has a high EUV transmittance and is unlikely to generate particles even if damaged.

[0065] The main layer 12 is composed of metal beryllium. However, the main layer 12 does not need to be composed entirely of metal beryllium, and preferably 98.0% by weight or more, more preferably 99.0% by weight or more, and further preferably 99.5% by weight or more of the main layer 12 can be composed of metal beryllium. In this way, an EUV transparent film having a high EUV transmittance at a practical level can be produced. The thickness of the main layer 12 is preferably 10 to 70 nm, more preferably 15 to 50 nm, and further preferably 20 to 35 nm.

[0066] The surface layer 14 is used to protect the metal beryllium layer, that is, the main layer 12, and even if the EUV transparent film 10 is damaged, the film is rolled up and does not contact the optical network 18, so that no particles P are generated. Therefore, the surface layer 14 is provided on the first surface 12a and the second surface 12b of the main layer 12, thereby controlling the stress of both surfaces of the main layer 12. The surface layer 14 typically contains at least one selected from the group consisting of beryllium nitride, beryllium oxynitride and beryllium oxide as a main component, but from the viewpoint of controlling stress, the surface layer 14 contains at least one fluoride selected from beryllium fluoride, beryllium fluornitride, beryllium oxyfluoride and beryllium fluoride nitride. Among them, the surface layer 14 preferably contains beryllium fluoride, beryllium fluoride nitride, beryllium oxyfluoride or beryllium fluoride nitride. Here, the "main component" in the surface layer 14 refers to a component that occupies 55% by weight or more, preferably 60% by weight or more, more preferably 65% ​​by weight or more, and further preferably 70% by weight or more of the surface layer 14. The fluorine atom content at the outermost surface of the surface layer 14 is preferably 4 to 50 atomic%, more preferably 6 to 40 atomic%, and further preferably 8 to 35 atomic%.

[0067] As described above, the surface layer 14 preferably contains (typically as a main component) at least one selected from the group consisting of beryllium nitride, beryllium oxynitride, and beryllium oxide. More preferably, the surface layer 14 contains: (i) beryllium fluoride and beryllium nitride, (ii) beryllium fluoride and beryllium oxynitride, (iii) beryllium fluoride and beryllium oxide, or (iv) beryllium fluoride, beryllium oxide, and beryllium nitride. It should be noted that the term "beryllium nitride" in this specification refers not only to a stoichiometric composition such as Be3N2, but also to a composition that allows Be3N2. 2-x (where 0<x<2) is a generalized composition of a non-stoichiometric composition. The same applies to other compound names such as beryllium oxynitride, beryllium oxide, beryllium fluoronitride, beryllium oxyfluoride, and beryllium oxyfluoronitride.

[0068] In the exposure process, from the viewpoint of stress control, it is preferred that the surface layer 14 at the first surface 12a is disposed on the side of the main layer 12 opposite to the optical grid 18 side, and the surface layer 14 at the second surface 12b is disposed on the optical grid 18 side of the main layer 12. Figure 2CAs shown, even if the EUV transparent film 10 is damaged, the EUV transparent film 10 can be rolled up to the first surface side (the side opposite to the optical network side) without contacting the optical network 18, and particles P are not easily generated. In order to achieve the above state well when the EUV transparent film 10 is damaged, the thickness of the surface layer 14 at the first surface 12a is preferably 1.1 times or more of the thickness of the surface layer 14 at the second surface 12b, more preferably 1.1 to 3.5 times, and further preferably 1.2 to 3 times. In addition, the fluorine atom concentration at the outermost surface of the surface layer 14 on the first surface 12a side is preferably 1.5 times or more of the fluorine atom concentration at the outermost surface of the surface layer 14 on the second surface 12b side, more preferably 1.5 to 3.4 times, and further preferably 1.7 to 3.0 times. Alternatively, when the thickness of the surface layer 14 at the first surface 12a is greater than the thickness of the surface layer 14 at the second surface 12b, and the fluorine atom concentration at the outermost surface of the surface layer 14 on the first surface 12a side is higher than the fluorine atom concentration at the outermost surface of the surface layer 14 on the second surface 12b side, it is preferred to satisfy A×B≥2.0 (wherein A is the ratio of the thickness of the surface layer 14 at the first surface 12a to the thickness of the surface layer 14 at the second surface 12b, and B is the ratio of the fluorine atom concentration at the outermost surface of the surface layer 14 on the first surface 12a side to the fluorine atom concentration at the outermost surface of the surface layer 14 on the second surface 12b side), more preferably satisfy 3.5≥A×B≥2.0, and further preferably satisfy 3.0≥A×B≥2.0. Here, the "outermost surface" of the surface layer 14 refers to the surface of the surface layer 14 on the opposite side of the main layer 12 side (the first surface 12a or the second surface 12b). By making the thickness and / or fluorine atom concentration of the surface layer 14 on the first surface 12 a and the surface layer 14 on the second surface 12 b different in this way, the stress on both surfaces of the EUV transparent film can be more effectively controlled, and the above-mentioned effect can be well achieved.

[0069] The thickness of the surface layer 14 at the first surface 12a is preferably 0.3 to 3.0 nm, more preferably 0.5 to 2.5 nm, and further preferably 0.8 to 2.2 nm. The thickness of the surface layer 14 at the second surface 12b is typically thinner than the surface layer 14 at the first surface 12a, preferably 0.2 to 2.8 nm, more preferably 0.4 to 2.3 nm, and further preferably 0.6 to 2.0 nm.

[0070] The fluorine atom concentration at the outermost surface of the surface layer 14 on the first surface 12a side is preferably 4 to 50 atomic %, more preferably 6 to 40 atomic %, and further preferably 8 to 35 atomic %. The fluorine atom concentration at the outermost surface of the surface layer 14 on the second surface 12b side is preferably lower than the fluorine atom concentration at the outermost surface of the surface layer 14 on the first surface 12a side, and is preferably 1 to 45 atomic %, more preferably 3 to 35 atomic %, and further preferably 6 to 25 atomic %.

[0071] The surface layer 14 preferably has a nitrogen concentration gradient region in which the nitrogen concentration decreases as it approaches the main layer 12. That is, as described above, the composition of the nitride that may be contained in the surface layer 14 may include a stoichiometric composition such as Be3N2 to Be3N 2-x (where 0<x<2) is a non-stoichiometric composition. In this case, when the surface layer 14 contains nitrides, the nitrides are preferably of a gradient composition whose composition approaches the beryllium-rich composition as it approaches the main layer 12. Accordingly, the adhesion between the surface layer 14 and the main layer 12 (i.e., the metal beryllium layer) can be improved, and the stress caused by the thermal expansion difference between the two layers can be alleviated. That is, the adhesion between the two layers can be improved to suppress peeling, or the two layers can be made less likely to peel off as a thermal expansion mitigation layer between the two layers when EUV light is absorbed and the temperature reaches a high temperature. The thickness of the nitrogen concentration gradient region is preferably less than the thickness of the surface layer 14. That is, the entire region of the thickness of the surface layer 14 is not required to be a nitrogen concentration gradient region. For example, it is preferred that only a portion of the thickness of the surface layer 14, such as a region preferably 10 to 70% of the thickness of the surface layer 14, and more preferably a region 15 to 50% of the thickness of the surface layer 14 is a nitrogen concentration gradient region.

[0072] The EUV transparent film 10 preferably has a main region for EUV transmission in the form of a self-supporting film. That is, it is preferred that only the outer edge of the EUV transparent film 10 has a substrate (e.g., Si substrate) used during film formation remaining in the form of a boundary. In other words, it is preferred that no substrate (e.g., Si substrate) remains in the main region other than the outer edge, that is, the main region is composed of only the main layer 12 and the surface layer 14.

[0073] The EUV permeable film 10 may have a high EUV transmittance at a practical level, and its EUV transmittance is preferably 91% or more, more preferably 92% or more, and further preferably 93% or more. The higher the EUV transmittance, the better, and therefore, the upper limit is not particularly limited, and is ideally 100%, but the EUV transmittance of the EUV permeable film 10 may typically be 99% or less, more typically 98% or less, and further typically 95% or less.

[0074] Manufacturing method

[0075] The EUV transparent film of the present invention can be produced as follows, that is, after forming a laminated film to be made into an EUV transparent film on a Si substrate, the unnecessary part of the Si substrate is etched away with XeF2 to form a self-standing film, and the film is fluorinated to produce the EUV transparent film. Therefore, as described above, the main part of the EUV transparent film is in the form of a self-standing film without any remaining Si substrate.

[0076] (1) Preparation of Si substrate

[0077] First, a Si substrate for forming a laminated film thereon is prepared. After a laminated film including a main layer 12 and a surface layer 14 is formed on the Si substrate, the main area (i.e., the area to be made into a self-supporting film) except for the edge portion is removed by XeF2 etching. Therefore, in order to perform etching efficiently in a short time, it is preferred to thin the thickness of the Si substrate in the area to be made into a self-supporting film in advance. Therefore, it is expected that a mask corresponding to the EUV transmission shape is formed on the Si substrate using a conventional semiconductor process, and the Si substrate is etched using wet etching to thin the thickness of the main area of ​​the Si substrate to a specified thickness. The wet-etched Si substrate is cleaned and dried, thereby preparing a Si substrate having a cavity formed using wet etching. It should be noted that as a wet etching mask, as long as it is a material with corrosion resistance to the wet etching liquid for Si, for example, SiO2 is preferably used. In addition, as a wet etching liquid, it is sufficient to be able to etch Si, without particular limitation. For example, if TMAH (tetramethylammonium hydroxide) is used under appropriate conditions, it can be etched very well with anisotropic etching for Si, so it is preferred.

[0078] (2) Formation of laminated films

[0079] The formation of the stacked film can be carried out by any film forming method. As an example of a preferred film forming method, sputtering can be cited. In the case of making a stacked film of a three-layer structure of beryllium nitride / beryllium / beryllium nitride, it is preferred to use sputtering using a pure Be target to make a beryllium film as the main layer 12, and to use reactive sputtering to make a beryllium nitride film as the surface layer 14. The reactive sputtering can be carried out as follows. For example, in sputtering using a pure Be target, nitrogen gas is introduced into the chamber so that beryllium and nitrogen react to generate beryllium nitride. In addition, as another method, beryllium nitride can be made as follows, that is, after forming a beryllium film, nitrogen plasma is irradiated to cause beryllium to undergo a nitridation reaction, thereby generating beryllium nitride. In short, the synthesis method of beryllium nitride is not limited to the above method. It should be noted that the beryllium target for forming the beryllium nitride film and the beryllium target for forming the beryllium film are preferably separate beryllium targets, but the same target may be used for forming the beryllium nitride film and the beryllium film. It should be noted that the beryllium nitride film and the beryllium film may be formed in a sputtering device with one chamber as in the embodiment described later, or the beryllium nitride film and the beryllium film may be formed in separate chambers using a sputtering device with two chambers.

[0080] In the case of forming a nitrogen concentration gradient region, when the film formation of beryllium nitride is switched to the film formation of metal beryllium, the introduction of nitrogen gas is stopped from the middle while sputtering is continued, and the film formation of metal beryllium is switched. Accordingly, as the concentration of nitrogen gas decreases, a region is formed in which the nitrogen concentration in the formed film decreases along the thickness direction. On the other hand, in the case of switching from metal beryllium to beryllium nitride, contrary to the above, if the introduction of nitrogen gas is started from the middle while sputtering is continued, a nitrogen concentration gradient region can be formed. By adjusting the time for changing the concentration of nitrogen gas, the thickness of the nitrogen concentration gradient region can be controlled.

[0081] (3) Self-supporting membrane and fluorination

[0082] The unnecessary part of the Si substrate except the outer edge portion remaining in the form of the boundary (border) of the Si substrate formed with the composite film is removed by etching with XeF2, and the self-supporting film of the composite film is carried out. In this etching process, when the etching of Si is carried out in the cavity portion so that Si disappears, the back side of the composite film (the face of the cavity side in contact with the Si substrate) is exposed, and a fluorination reaction occurs, thereby forming the surface layer at the second face of the principal layer. On the other hand, a fluorination reaction also occurs in the surface side of the composite film (the face exposed from the beginning on the opposite side of the Si substrate), thereby forming the surface layer at the first face of the principal layer, but the surface side is exposed from the beginning, therefore, a fluorination reaction occurs at the beginning of the self-etching process. That is, the exposure time in XeF2 is different between the surface side and the back side of the composite film, and the surface side is in contact with XeF2 for a long time, and there are more fluorides. Therefore, the fluorine atom concentration of the surface layer at the first face is higher than the fluorine atom concentration of the surface layer at the second face. The type of fluoride varies depending on the material of the beryllium layer that reacts with XeF2, the reaction temperature, the reaction time, etc. When beryllium nitride is formed on the outermost layer of the composite film, beryllium fluoride, beryllium oxyfluoride, beryllium fluoronitride, beryllium oxynitride, etc. are confirmed to be generated.

[0083] Example

[0084] The present invention will be further specifically described by the following examples.

[0085] Example 1

[0086] In order to confirm how the stress of the beryllium composite film (a laminated film of a three-layer structure of beryllium nitride / beryllium / beryllium nitride) changes when fluorination occurs, a composite film is formed on a Si substrate, and the stress change of the composite film before and after fluorination is confirmed. First, a SiO2 film is formed on a single side of the Si substrate by thermal oxidation, so that the single side is not etched by the XeF2 used for fluorination of the composite film. A beryllium composite film is formed on the surface of the Si substrate opposite to the surface on which the SiO2 film is formed. Specifically, first, the Si substrate on which the SiO2 film is formed is fixed to a sputtering device, and a pure Be target is installed. The chamber is evacuated and adjusted to an internal pressure of 0.5 Pa and a flow ratio of argon and nitrogen of 1:1, and reactive sputtering is performed. When the beryllium nitride is stacked for 2 nm, the reactive sputtering is terminated. Next, without introducing nitrogen, sputtering is performed only with argon, and sputtering is terminated when the beryllium is stacked for 25 nm. Afterwards, nitrogen is introduced again in the same manner as at the beginning, and reactive sputtering is performed simultaneously. When the beryllium nitride is stacked for 2nm, reactive sputtering is terminated. A beryllium composite film of beryllium nitride (Be3N2) 2nm / metal beryllium (Be) 25nm / beryllium nitride (Be3N2) 2nm is formed in this way. The warping amount of the Si substrate before and after the composite film is formed is measured. As a result, the warping amount of the Si substrate after the composite film is formed is greater than the warping amount of the Si substrate before the composite film is formed. Therefore, it is confirmed that tensile stress acts on the composite film. Next, the Si substrate is exposed to XeF2 gas to fluorinate the beryllium nitride of the composite film. The warping amount of the Si substrate before and after fluorination is measured. As a result, the warping amount of the Si substrate after fluorination is greater than the warping amount of the Si substrate before fluorination. Therefore, it is confirmed that the tensile stress of the composite film after fluorination increases. As can be seen from the above results, there is stress inherent in the beryllium composite film, and the stress can be controlled by fluorination. Therefore, the stress on both sides of the EUV transparent film (for example, beryllium composite film) can be different by fluorination, and when the EUV transparent film is damaged, the EUV transparent film can be rolled up by utilizing the stress difference.

[0087] Example 2

[0088] according to Figure 3A and Figure 3B The steps shown are as follows to produce a composite self-supporting film (EUV transparent film) with a three-layer structure of surface layer / main layer / surface layer.

[0089] (1) Preparation of Si substrate

[0090] Prepare a Si wafer 20 (8 inches (20.32 cm) in diameter) Figure 3A (a)). On both sides of the Si wafer 20, a SiO2 film 22 with a thickness of 50 nm is formed by thermal oxidation. Figure 3A(b)). A resist is applied on both sides of the Si wafer 20, and exposure and development are performed in such a manner that a resist hole of 110 mm×145 mm can be formed on one side to form a resist mask 24 for SiO2 etching ( Figure 3A (c)). One surface of the substrate is wet-etched with hydrofluoric acid to remove the exposed portion of the SiO2 film 22, thereby forming a SiO2 mask 22a ( Figure 3A (d)). The resist mask 24 for SiO2 etching is removed by an ashing device ( Figure 3A (e)). Then, Si is etched using TMAH solution. The etching rate is measured in advance and the etching time is set to a target Si substrate thickness of 50 μm. ( Figure 3A (f)). Finally, the SiO2 film 22 formed on the surface where Si etching is not performed is removed and cleaned by hydrofluoric acid to prepare the Si substrate 28 ( Figure 3B (g)). Regarding the shape of the Si substrate, it can be cut using laser 30 as needed ( Figure 3B (h)), set to the desired shape ( Figure 3B (i)) In this way, a Si substrate 28 was prepared in which a cavity 26 of 110 mm×145 mm was provided in the center of an 8-inch (20.32 cm) Si wafer 20 and the Si thickness of the cavity 26 portion was 50 μm.

[0091] (2) Formation of composite membrane

[0092] The Si substrate 28 having the cavity 26 obtained in the above (1) is formed into a composite film having a three-layer structure of beryllium nitride / beryllium / beryllium nitride as follows: Figure 3B (i)). First, fix the Si substrate 28 to the sputtering device and install a pure Be target. Evacuate the chamber and adjust the internal pressure to 0.5 Pa and the flow ratio of argon and nitrogen to 1:1, and perform reactive sputtering. When the beryllium nitride stacks 2nm, the reactive sputtering is terminated. Next, without introducing nitrogen, only sputtering with argon is performed. When the beryllium stacks 25nm, the sputtering is terminated. After that, nitrogen is introduced again in the same way as at the beginning, and reactive sputtering is performed at the same time. When the beryllium nitride stacks 2nm, the reactive sputtering is terminated. In this way, a composite film 11 of beryllium nitride (Be3N2) 2nm / metal beryllium (Be) 25nm / beryllium nitride (Be3N2) 2nm is formed.

[0093] (3) Self-supporting membrane and fluorination

[0094] In the chamber of a XeF2 electroetcher capable of processing an 8-inch (20.32 cm) substrate, the Si substrate 28 with the composite film 11 prepared in (2) above is fixed. The chamber is fully evacuated. At this time, if there is residual moisture in the chamber, it will react with the XeF2 gas to produce hydrofluoric acid, causing corrosion of the electroetcher or unexpected etching, so it is fully evacuated. As needed, the chamber is repeatedly evacuated and nitrogen is introduced to reduce residual moisture. After fully evacuating, the valve between the XeF2 raw material bottle and the preparation chamber is opened. As a result, XeF2 sublimates and XeF2 gas is also accumulated in the preparation chamber. After the XeF2 gas is fully accumulated in the preparation chamber, the valve between the preparation chamber and the chamber is opened to introduce the XeF2 gas into the chamber. The XeF2 gas decomposes into Xe and F, and F reacts with Si to generate SiF4. The boiling point of SiF4 is -95°C, so the generated SiF4 evaporates quickly, and the newly exposed Si substrate reacts with F. After Si etching is performed and the F in the chamber is reduced, the chamber is evacuated and XeF2 gas is introduced into the chamber again to perform etching. Vacuuming, XeF2 gas introduction and etching are repeated in this way, and etching is continued until the Si wafer 20 corresponding to the self-supporting film portion disappears. After the unnecessary part of the Si substrate disappears, the etching is terminated. In this way, a composite self-supporting film with a Si border is obtained as an EUV transparent film 10 ( Figure 3B (j)). It should be noted that during etching, F also reacts with the beryllium nitride layer on the first surface (the surface on the opposite side to the Si wafer 20) and the second surface (the surface on the Si wafer 20 side) of the beryllium layer in the composite film 11, so that a pair of surface layers in the EUV transparent film 10 obtained in this way contains fluoride.

[0095] (4) TEM / EDS of EUV-transmitted film cross section

[0096] A sample obtained by cutting out a cross section of an EUV-transmitting film by focused ion beam (FIB) processing was observed using a transmission electron microscope (TEM) (manufactured by JEOL Ltd., JEM-2100F) at 200 kV, and elemental analysis was performed using an EDS analyzer (manufactured by JEOL Ltd., JED-2300T) at an acceleration voltage of 5 keV in element mapping and point analysis mode. As a result, it was found that the thickness of the main layer was 24 nm, the thickness of the surface layer at the first surface was 2.3 nm, and the thickness of the surface layer at the second surface was 1.9 nm. In the surface layer at the second surface, only a trace amount of fluorine was detected on its outermost surface, so it was judged that beryllium fluoride nitride was generated on the outermost surface of the surface layer at the second surface. On the other hand, fluorine was detected in the surface layer at the first surface at a deeper position than the surface layer at the second surface, so it was judged that more beryllium fluoride nitride was generated in the surface layer at the first surface. In addition, nitrogen and a trace amount of oxygen were also detected from the portion where fluorine was detected in the surface layer at the first and second surfaces. It can be seen from this that the fluorine atom concentration in the surface layer at the first surface of the EUV transparent film is higher than the fluorine atom concentration in the surface layer at the second surface, and the fluoride generated in the surface layer (the first surface and the second surface) contains beryllium fluoronitride as the main component, and contains trace amounts of beryllium fluoronitride oxide and / or beryllium fluoride oxide.

[0097] In addition, in the evaluation of (4) above, the fluorine atom concentration at the outermost surface of the surface layer on the first surface side is 32 atomic%, and the fluorine atom concentration at the outermost surface of the surface layer on the second surface side is 18 atomic%. It can be seen from this that the ratio A of the thickness of the surface layer at the first surface to the thickness of the surface layer at the second surface is 1.21, and the ratio B of the fluorine atom concentration at the outermost surface of the surface layer on the first surface side to the fluorine atom concentration at the outermost surface of the surface layer 14 on the second surface side is 1.78, so A×B=2.15.

[0098] (5) Observation of the state of EUV transparent film after damage

[0099] The center of the EUV transparent film was pierced with a needle. As a result, the damaged self-supporting film rolled up toward the first surface, and no particles were observed. That is, the state of the EUV transparent film after damage was Figure 2C Status shown.

[0100] In the EUV transparent film of the present invention, the stress is different between the first and second surfaces of the surface layer. Therefore, even if the EUV transparent film is damaged, the damaged EUV transparent film will roll up to the first surface side (the side opposite to the optical network side). Therefore, it is possible to suppress the EUV transparent film from swinging and contacting the optical network or the boundary to generate particles.

Claims

1. An EUV transparent film, wherein: have: a main layer, the main layer being composed of metal beryllium and having a first surface and a second surface; and A pair of surface layers, the pair of surface layers are provided on the first surface and the second surface of the main layer, and contain at least one fluoride selected from the group consisting of beryllium fluoride, beryllium fluoronitride, beryllium oxyfluoride, and beryllium oxynitride fluoride.

2. The EUV transparent film according to claim 1, wherein: The surface layer includes beryllium fluoride.

3. The EUV transparent film according to claim 1, wherein The surface layer includes beryllium fluoronitride.

4. The EUV transparent film according to claim 1, wherein The surface layer includes beryllium oxyfluoride.

5. The EUV transparent film according to claim 1, wherein: The surface layer includes beryllium oxyfluoride and nitride.

6. The EUV transparent film according to claim 1, wherein: The surface layer further includes at least one selected from the group consisting of beryllium nitride, beryllium oxynitride, and beryllium oxide.

7. The EUV transparent film according to claim 6, wherein: The surface layer includes beryllium fluoride and beryllium nitride.

8. The EUV transparent film according to claim 6, wherein: The surface layer includes beryllium fluoride and beryllium oxynitride.

9. The EUV transparent film according to claim 6, wherein: The surface layer includes beryllium fluoride and beryllium oxide.

10. The EUV transparent film according to claim 6, wherein: The surface layer includes beryllium fluoride, beryllium oxide and beryllium nitride.

11. The EUV transparent film according to any one of claims 1 to 10, wherein The thickness of the surface layer at the first surface is 1.1 times or more the thickness of the surface layer at the second surface.

12. The EUV transparent film according to any one of claims 1 to 10, wherein The fluorine atom concentration at the outermost surface of the surface layer on the first surface side is 1.5 times or more the fluorine atom concentration at the outermost surface of the surface layer on the second surface side.

13. The EUV transparent film according to any one of claims 1 to 10, wherein The thickness of the surface layer at the first surface is greater than the thickness of the surface layer at the second surface, and the fluorine atom concentration at the outermost surface of the surface layer on the first surface side is higher than the fluorine atom concentration at the outermost surface of the surface layer on the second surface side, When the ratio of the thickness of the surface layer at the first surface to the thickness of the surface layer at the second surface is set to A, and the ratio of the fluorine atom concentration at the outermost surface of the surface layer on the first surface side to the fluorine atom concentration at the outermost surface of the surface layer on the second surface side is set to B, A×B≥2.0 is satisfied.

Citation Information

Patent Citations

  • Method for forming carbon nanotube pellicle membrane

    JP2018194840A

  • Pellicle and pellicle assembly

    JP2018537720A